Impact of Terms-of-Trade on Slovakia, the Czech Republic, and Croatia in the Short Run - Karol Szomolányi; Martin Lukáčik; Adriana Lukáčiková (Naše gospodarstvo/Our economy, 2017)
The terms-of-trade shocks are not main source of business cycles in three post- communist countries (i.e., Slovakia, the Czech Republic, and Croatia). The zero or negative reactions of the trade balance in terms-of-trade positive shocks in the countries exhibit the Obstfeld-Svensson-Razin effect, according to which the Harberger-Laursen-Metzler positive effect on terms-of-trade indicates that the smaller the trade balance, the more persistent the terms-of-trade shock is. The conclusions come from the structural vector autoregressive analysis of the cyclical components of terms-of-trade, trade balance, output, consumption, and investment in three post-communist countries.